2006
DOI: 10.1152/ajpcell.00075.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of calreticulin in the sensitivity of myocardiac H9c2 cells to oxidative stress caused by hydrogen peroxide

Abstract: Ihara, Yoshito, Yoshishige Urata, Shinji Goto, and Takahito Kondo. Role of calreticulin in the sensitivity of myocardiac H9c2 cells to oxidative stress caused by hydrogen peroxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 62 publications
2
38
2
Order By: Relevance
“…Cultured cells were harvested and lysed in lysis buffer [20 mmol/L Tris-HCl (pH 7.5), 130 mmol/L NaCl, and 1% NP40 including protease inhibitors (20 Amol/L amidinophenyl methanesulfonyl fluoride, 50 Amol/L pepstatin, and 50 Amol/L leupeptin)]. Protein samples were subjected to SDS-PAGE and then transferred to a nitrocellulose membrane as described (21). The membrane was blocked and then incubated with the primary antibody in TBS containing 0.05% Tween 20.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultured cells were harvested and lysed in lysis buffer [20 mmol/L Tris-HCl (pH 7.5), 130 mmol/L NaCl, and 1% NP40 including protease inhibitors (20 Amol/L amidinophenyl methanesulfonyl fluoride, 50 Amol/L pepstatin, and 50 Amol/L leupeptin)]. Protein samples were subjected to SDS-PAGE and then transferred to a nitrocellulose membrane as described (21). The membrane was blocked and then incubated with the primary antibody in TBS containing 0.05% Tween 20.…”
Section: Methodsmentioning
confidence: 99%
“…CRT is a multifunctional protein involved in many biological processes that include the regulation of Ca 2+ homeostasis (16), intercellular or intracellular signaling, gene expression (17), glycoprotein folding (18), and nuclear transport (19). We found that overexpression of CRT enhanced apoptosis in myocardiac H9c2 cells under conditions inductive to differentiation with retinoic acid (20) or under oxidative stress (21). Moreover, CRT regulates p53 function to induce apoptosis by affecting the rate of degradation and nuclear localization of p53 (12).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…H9c2 cells were seeded in quadruplicate in 24-well plates and the experimental groups were: i) control: CTRL, absence of any additional treatment; ii) H 2 O 2 : H9c2 were exposed to 50µM H 2 O 2 for 2 hours [20]; iii) CST: cells were exposed to CST 75nM for 3 hours; iv) CST+H 2 O 2 : cells were exposed to CST for 1 hour, then CST plus H 2 O 2 were continued for other 2 hours.…”
Section: Cell Culture and Drug Treatmentmentioning
confidence: 99%
“…In brief, JC-1 (10µM) was added to cultured cells [46] in control and after the treatment with H 2 O 2 (50µM) [20] with or without CST (75 nM). The ratio between red and green JC-1 florescence was taken as an index of mitochondrial membrane potential [25].…”
Section: Measurement Of Mitochondrial Potentialmentioning
confidence: 99%